2020
DOI: 10.3389/fnhum.2020.00174
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Template MRI Is a Valid and Reliable Alternative to Individual MRI for Spatial Tracking in Navigated TMS Studies in Healthy Subjects

Abstract: Objectives: Navigated transcranial magnetic stimulation (nTMS) provides significant benefits over classic TMS. Yet, the acquisition of individual structural magnetic resonance images (MRI individual ) is a time-consuming, expensive, and not feasible prerequisite in all subjects for spatial tracking and anatomical guidance in nTMS studies. We hypothesize that spatial transformation can be used to adjust MRI templates to individual head shapes (MRI warped ) and that TMS parameters do not differ between nTMS usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Therefore, a successful registration relies on reliable mapping between individual anatomy and the group-based template. Indeed, while individualized anatomical mapping is the gold standard, recent evidence suggests that templatebased MNI localization can be used as an accurate and effective alternative to individualized anatomical localization for TMS studies (Fleischmann et al, 2020). Perhaps more importantly, given that the functional organization of LIFC can vary substantially from individual to individual as discussed above (Mahowald & Fedorenko, 2016;Fedorenko et al, 2012), a need for individualized functional localizers is critical for future research, arguably more so than individualized anatomical targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a successful registration relies on reliable mapping between individual anatomy and the group-based template. Indeed, while individualized anatomical mapping is the gold standard, recent evidence suggests that templatebased MNI localization can be used as an accurate and effective alternative to individualized anatomical localization for TMS studies (Fleischmann et al, 2020). Perhaps more importantly, given that the functional organization of LIFC can vary substantially from individual to individual as discussed above (Mahowald & Fedorenko, 2016;Fedorenko et al, 2012), a need for individualized functional localizers is critical for future research, arguably more so than individualized anatomical targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a successful registration relies on reliable mapping between individual anatomy and the group‐based template. Indeed, while individualized anatomical mapping is the gold standard, recent evidence suggests that template‐based MNI localization can be used as an accurate and effective alternative to individualized anatomical localization for TMS studies (Fleischmann et al, 2020). Perhaps more importantly, given that the functional organization of LIFC can vary substantially from individual to individual as discussed above (Mahowald & Fedorenko, 2016; Fedorenko et al, 2012), a need for individualized functional localizers is critical for future research, arguably more so than individualized anatomical targeting.…”
Section: Discussionmentioning
confidence: 99%
“…We checked that the use of individual MRI versus MRI template did not affect the natural frequency variability, although it may have affected the variability of the first component amplitude. Recent findings have suggested that brain responses to TMS can be equivalent when using an MRI template if a sufficient number of registration points are used during the curvilinear reconstruction of the participant's head (Fleischmann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%